The Impact of ESG Disclosure, Financial Performance, and Leverage on Corporate Tax Avoidance: Evidence with Firm Size as a Moderating Variable - Alistiqomah, Chintya Istigfarah; Putri Awalina; Siti Isnaniati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This research investigates how Environmental, Social, and Governance (ESG) disclosure, financial performance, and leverage influence corporate tax avoidance, while considering firm size as a moderating factor. A quantitative research design is employed using panel data from coal mining subsector firms listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 period. The study analyzes 86 firm-year observations selected through purposive sampling. Data processing is conducted using multiple linear regression and Moderated Regression Analysis (MRA) with the Statistical Package for the Social Sciences (SPSS). Tax avoidance is assessed using the effective tax rate (ETR), ESG disclosure is quantified through an index based on Global Reporting Initiative (GRI) standards, financial performance is represented by return on assets (ROA), leverage is measured by the debt-to-assets ratio (DAR), and firm size is calculated as the natural logarithm of total assets. The empirical results reveal that ESG disclosure significantly affects tax avoidance, whereas financial performance and leverage do not show significant effects in the baseline regression model. Moreover, firm size does not moderate the relationship between ESG disclosure and tax avoidance; however, it significantly moderates the relationships between financial performance and tax avoidance and between leverage and tax avoidance. These results suggest that firm size enhances the role of financial capacity and capital structure in shaping corporate tax behavior, while the influence of ESG disclosure remains relatively consistent across firms. This study contributes empirical evidence from the coal mining industry and provides practical implications for regulators and corporate management in strengthening tax governance.